Editorial: Triggering a Paradigm Shift in Public Policy Making in Nepal - Upreti, Bishnu Raj; Acharya, Bikram (Nepal Public Policy Review, 2022)
When we launched ‘Nepal Public Policy Review (NPPR)’ as a policy journal last year, we were not sure how the stakeholders – academic researchers and the policy community in particular – would react to it. A year down the line, NPPR has been a platform to engage academic researchers and the policy community in critical discussion and reflection on how Nepal’s public policy discourse should be reimagined and restructured. We are happy that a frank and honest discussion has started. We hope the discussion will trigger a paradigm shift in the way public policies are envisioned, developed and implemented. Such a shift is long overdue in Nepal.